Case report: Leukemia cutis as the first manifestation of chronic neutrophilic leukemia in a 6-year-old girl - Zhou, Ya Bin; Yao, Jia Feng; Xu, Zi Gang; Wu, Rui Hui (Frontiers in Pediatrics, 2022)
Chronic neutrophilic leukemia (CNL) is a rare BCR-ABL negative myeloproliferative neoplasm that usually affects older adults with a poor prognosis. Leukemia cutis is an extramedullary manifestation of leukemia and may be misdiagnosed by dermatologists. Here, we describe a case of CNL in a 6-year-old Chinese girl with leukemia cutis as the first manifestation. Her skin rashes failed to attract the attention of dermatologists in early stages. The diagnosis was confirmed by peripheral smear, bone marrow studies, genomic analysis and skin biopsy.